Gardner syndrome with odontogenic sinusitis: A case report. Issue 6 (23rd June 2021) - Saito, Kosuke; Sekine, Motoki; Goto, Fumiyuki; Yamamoto, Hikaru; Kaneda, Shoji; Sakai, Akihiro; Iijima, Hiroaki; Yamauchi, Mayu; Yamazaki, Aritomo; Okami, Kenji
Abstract: Gardner syndrome with odontogenic sinusitis is rare but should be suspected in patients with multiple osteomas of the skull and facial bones, excess teeth, impacted teeth, and odontomas. Early diagnosis and treatment of GS may improve prognosis. Abstract : Gardner syndrome with odontogenic sinusitis is rare but should be suspected in patients with multiple osteomas of the skull and facial bones, excess teeth, impacted teeth, and odontomas. Early diagnosis and treatment of GS may improve prognosis.